Influence of Nutrients an Water Stress on Germination of some Pea Cultivars Pisum Sativum - Ghafour, Noori- Hasan (Sulaimani Journal for Pure and Applied Sciences, 2000)
An investigation was conducted to study the germination behaviour of different Peas cultivars under a combination of NP solution and a water-stress treatments. Results indicate that the nutrient combination treatments caused in the non-significant increase in the germination rate, radicle length and the radicle speed elongation, in addition to the abnormal seedling. Significant differences were found among cultivars in their water stress resistance as mean germination time, drought resistance index, and germination rate.